Efficacy of Xanthomonas crude lipopolysaccharide on the control of the tomato bacterial spot - Halfeld-Vieira, Bernardo de Almeida; Simões, Camila Tonelotti [UNESP]; Carvalho, Valdeir Nunes [UNESP] (Elsevier, 2023)
Plants can recognize pathogen-derived molecules and trigger systemic acquired resistance. In plant pathogenic bacteria, several of these elicitors are structural components constitutively present in the pathogen, such as cell wall lipopolysaccharide (LPS). This research aims at evaluating the ability of crude LPS from incompatible Xanthomonas strains to control tomato bacterial spot caused by X. euvesicatoria pv. perforans. Crude LPS from strains that demonstrated the ability to be recognized by tomato plants were evaluated through spray, leaf infiltration, and soil applications. The LPS from X. axonopodis pv. passiflorae strain CMAA 1829 was tested three times, showing a greater reduction both in the number of lesions per leaflet and in disease severity when applied on soil. However, chlorophyll content in tomato leaflets presented a brief reduction in the short term. Peroxidase (PO) and polyphenoloxidase activities in plants exposed to crude LPS from CMAA 1829 increased in the first day after pathogen inoculation (DAI), but only PO activity remained high throughout at least the 15 DAI. Results show that the use of crude LPS from host-incompatible strains of Xanthomonas to trigger systemic resistance can configure a valuable asset to control tomato bacterial spot.
Keywords: Elicitor; Induced systemic resistance; Pathogen/microbe-associated molecular patterns; Solanum lycopersicum; Xanthomonas euvesicatoria pv. perforans